(untitled) (Web of Humanities: Journal of Social Science and Humanitarian Research, 2025)
This article examines the role, application, and effectiveness of modern technical tools in the identification and apprehension of criminal offenders. Particular attention is given to the deployment of advanced biometric identification systems—including fingerprint scanning, facial recognition technologies, and iris scanning—as well as the integration of artificial intelligence algorithms, GPS-based geolocation systems, surveillance cameras, and unmanned aerial vehicles (drones) in contemporary law enforcement practices. The study analyses how these technologies enhance operational efficiency, accelerate investigative processes, and support evidence-based decision-making in criminal investigations. Practical examples and recent case studies are presented to illustrate the successful use of these tools in real-world scenarios. Furthermore, the article emphasizes the critical importance of the synergy between technological innovation and human expertise in strengthening crime prevention and ensuring public safety.